Fiber optics without fiber. - Willebrand, H.A.
Low-power infrared beams, which do not harm the eyes, are the means by which free-space optics (FSO) technology transmits data through the air between transceivers, or link heads, mounted on roof-tops or behind windows. It works over distances of several hundred meters to a few kilometers, depending upon atmospheric conditions. The authors believe that FSO could be the ultimate solution for high-speed residential access. Instead of hybrid fiber-coax systems, hybrid fiber-laser systems may turn out to be the best way to deliver high data rates directly to the home
Keywords: Free-space optics technology; High-speed residential access; Hybrid fiber-laser systems; Link heads; Low-power infrared beams; Optical communication; Transceivers